Mubodyna - dynamic analysis of multibody systems: a fortran program for dynamic analysis of planar multibody systems: user’s manual version 1.0 - Flores, Paulo (2010)
A FORTRAN Program for Dynamic Analysis of Planar Multibody Systems.